PENDAMPINGAN BELAJAR MATEMATIKA BAGI SISWA BERKEBUTUHAN KHUSUS SLOW LEARNER - Dian Permatasari; Riham Fahira Rantayu; Aulia Farida; Zahrina Salsabila; Muhammad Nauval Muwaffiq (Jurnal Penamas Adi Buana, 2022)
In Indonesia, an education system is implemented where students with special learning needs can get education in public schools. One type of child with special needs that is accepted by public schools is a slow learner. Slow learner children usually have various things during learning, such as difficulty in understanding abstract concepts, low motivation to learn, slow to understand material, and need to understand repetitive material. Therefore, community service is needed which aims to provide special assistance to slow learner students to help students learn mathematics. Partners in this service are 2 slow learner students from 2 schools in Yogyakarta. The stages of this service consist of 3 stages, namely the preparation, mentoring and evaluation stages of learning. The results of the service show that there is an increase in mathematical understanding for slow learner students. Students become easier to understand the mathematical material presented by various methods and teaching aids that have been developed by the team.